Prediction Of Diagenesis And Reservoir Quality Using Wireline Logs: Evidence From The Upper Triassic (raethian) Fluvial Reservoir Tags - Toual Field, Gassi Touil Area, Se Algeria - Mazouz, E.; Hamimed, M.; Yahiaoui, A.; El-ghali, M. A. K. (University of Eloued جامعة الوادي, 2017)
Reservoir quality is mainly controlled by environment deposit type and diagenesis processes. To investigate such subject we usually proceed to microscopic techniques. Absence of outcrops and missing of core samples let us use conventional wireline logs and core lab measurements as primary data. Direct lecture of well logs calibrated by core photos and wellsite description, well logs correlation and cross plots were our main methodology axis. Target of this study is the fluvial Shaly Sandstones of Upper Triassic (Rhaetian) reservoir (abreviated in French; TAGS) located in Toual field – SE of Algeria. The present investigation confirms the absence of clean sandstone levels in the studied reservoir. It detects also the presence of halite and clays (Illite) as cements in sandstone. The influence of illite on permeability was confirmed whereas porosity is less affected.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 02
Keywords: Diagenesis; Reservoir Quality; Well logs; Fluvial System; Triassic; Toual.